A copper paste, electrode, and preparation method and application thereof
Patent Information
- Application Number
- CN202411245861.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-09-05
AI Technical Summary
然而导电银浆作为市面导电浆料的主流,导致太阳能电池成本一直居高不下,若能用铜浆代替银浆作为太阳能电池栅线,则其成本将会大幅下降
[0045]The electrode and copper paste described in this application utilize nano-copper particles, which are composed of two or more copper nanoparticles connected together, to fill the voids between large-sized flake copper powders. The nano-copper particles have a three-dimensional shape with unequal diameters, which facilitates their matching with various shaped voids formed between multiple flake copper powders. Furthermore, their surfaces have more contact points with the flake copper powders and other nano-copper particles, increasing the contact area between the flake copper powders and the nano-copper particles, as well as among the copper particles themselves. This increases the conductive pathways between various conductive copper powders. The filling of nano-copper particles makes the electrode structure more compact, significantly reducing the electrode's bulk resistance and achieving conductivity comparable to electrodes prepared with silver paste. After sintering and curing, the nano-copper particles can also act as an auxiliary binder, improving the adhesion between the copper paste and the solar cell, resulting in a stronger connection between the electrode and the solar cell.
Smart Images

Figure BDA0005031201690000192 
Figure BDA0005031201690000211 
Figure BDA0005031201690000231
Abstract
Description
Technical Field
[0001] This application relates to the field of solar cells, specifically to a copper paste, an electrode, and its preparation method and application. Background Technology
[0002] In recent years, with the continuous improvement of the photoelectric conversion efficiency of solar cells, their importance in solving energy shortages and environmental pollution has become increasingly prominent, and they play a significant role in promoting the development of green energy. Conductive paste, as a crucial component of solar cells, plays a vital role in improving cell efficiency. However, conductive silver paste is the mainstream conductive paste on the market, causing the cost of solar cells to remain high. If copper paste could be used instead of silver paste for the grid lines of solar cells, the cost would be significantly reduced.
[0003] Existing conductive copper pastes use a traditional low-temperature curing method, which involves mixing an organic system (resin, curing agent, dispersant) with a conductive phase (copper powder). Due to the difference in conductivity between copper and silver, the electrical properties of the cured copper paste are inferior to those of the silver paste. Summary of the Invention
[0004] This application aims to provide an electrode that fills the gaps between large-sized flake copper powder with nano-copper particles, allowing them to directly contact the flake copper powder. This makes the conductive channels between the conductive particles more unobstructed, and the filling of nano-copper particles makes the electrode structure more compact, significantly reducing the bulk resistance of the electrode and achieving conductivity comparable to that of a silver electrode.
[0005] This application provides an electrode comprising copper nanoparticles and sheet-like copper powder, wherein the copper nanoparticles comprise at least two connected copper nanoparticles, and adjacent copper nanoparticles are connected by surface contact.
[0006] Furthermore, the median length of the copper nanoparticles is 150nm-700nm, and the median width of the copper nanoparticles is 40nm-400nm.
[0007] Furthermore, the nano-copper particles are linear copper particles formed by at least two interconnected copper nanoparticles, and / or
[0008] The copper nanoparticles are formed by bending and connecting at least two connected copper nanoparticles at a certain angle to form L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, quadrilateral copper particles, W-shaped copper particles, or polygonal copper particles with more than 5 sides.
[0009] Furthermore, the electrode also includes spherical copper powder.
[0010] Furthermore, in the copper powder, the mass percentage of the nano-copper particles is 0.5%-15%, the mass percentage of the flake-shaped copper powder is 35%-60%, and the mass percentage of the spherical copper powder is 35%-60%.
[0011] Furthermore, the median particle size of the spherical copper powder is 100nm-500nm.
[0012] Further, the tap density of the flake copper powder is 4.4–5 g / ml, and the tap density of the spherical copper powder is 4.3–4.9 g / ml; or
[0013] The specific surface area of the flaky copper powder is 0.4–0.7 m². 2 / g, the specific surface area of the spherical copper powder is 2.5-3.0m². 2 / g.
[0014] Furthermore, the median diameter of the flake copper powder is 2μm-8μm, and the median thickness is 100nm-500nm.
[0015] Furthermore, the electrode comprises a main body portion and a peripheral portion, the peripheral portion being located on both sides of the main body portion, wherein the width of the peripheral portion on either side does not exceed 5%-50% of the width of the main body portion; the median copper powder particle size of the peripheral portion is less than the median copper powder particle size of the main body portion of the gate line.
[0016] Furthermore, the copper powder in the peripheral portion includes the nano-copper particles, and the copper powder in the main body portion includes the flake-shaped copper powder and the nano-copper particles.
[0017] Furthermore, the width of the main body portion is 30-120 micrometers; or the width of the peripheral portion is 1-60 micrometers.
[0018] Furthermore, the electrode is prepared by screen printing.
[0019] This application also provides a copper paste comprising copper powder, the copper powder comprising nano-copper particles, flake copper powder, and optionally spherical copper powder, wherein the nano-copper particles comprise at least two connected copper nanoparticles, and adjacent copper nanoparticles are connected by surface contact.
[0020] Furthermore, the median length of the copper nanoparticles is 150nm-700nm, and the median width of the copper nanoparticles is 40nm-400nm.
[0021] Furthermore, the nano-copper particles are linear copper particles formed by at least two interconnected copper nanoparticles, and / or
[0022] The copper nanoparticles are formed by bending and connecting at least two connected copper nanoparticles at a certain angle to form L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, quadrilateral copper particles, W-shaped copper particles, or polygonal copper particles with more than 5 sides.
[0023] Furthermore, the copper powder also includes spherical copper powder, wherein the mass percentage of the nano-copper particles is 0.5%-15%, the mass percentage of the flake copper powder is 35%-60%, and the mass percentage of the spherical copper powder is 35%-60%.
[0024] Furthermore, the median diameter of the flake-shaped copper powder is 2μm-8μm, and the median thickness is 100nm-500nm; or
[0025] The median particle size of the spherical copper powder is 100nm-500nm.
[0026] Further, the tap density of the flake copper powder is 4.4–5 g / ml, and the tap density of the spherical copper powder is 4.3–4.9 g / ml; or
[0027] The specific surface area of the flaky copper powder is 0.4–0.7 m². 2 / g, the specific surface area of the spherical copper powder is 2.5-3.0m². 2 / g.
[0028] Furthermore, the copper paste further includes resin, solvent, curing agent, and optionally a curing accelerator, wherein the copper powder comprises 70-95 parts by weight, the resin comprises 5-15 parts by weight, the curing agent comprises 1-5 parts by weight, the solvent comprises 5-20 parts by weight, and the curing accelerator comprises 0-5 parts by weight; or,
[0029] The resin is selected from one or more of epoxy resin, acrylic resin, and phenolic resin; or,
[0030] The curing agent is selected from one or more of tertiary amine, isocyanate, imidazole, dicyandiamide, and acid anhydride curing agents; or,
[0031] The optional curing accelerator is a quaternary ammonium salt, an imidazolium ester, an imidazolium salt, or a substituted urea; or,
[0032] The solvent is selected from one or more of the following: divalent ester (DBE), diethylene glycol butyl ether, diethylene glycol butyl ether acetate, terpineol, dipropylene glycol butyl ether, and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, butyl acetate, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol dimethyl ether, dimethylformamide, N-methylpyrrolidone, diacetone alcohol, dimethylacetamide, γ-butyrolactone, butyl carbitol, butyl carbitol acetate, ethyl carbitol, ethyl carbitol acetate, dihydroterpineol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, dihydroterpineol acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.
[0033] This application also provides an electrode, which is obtained by screen printing the aforementioned copper paste.
[0034] This application also provides a method for preparing the aforementioned copper paste, which includes the following steps:
[0035] Preparation of copper nanoparticles;
[0036] Copper paste is prepared by mixing nano-copper particles with flake copper powder, spherical copper powder, resin, solvent, curing agent and optional curing accelerator.
[0037] The copper nanoparticles comprise at least two connected copper nanoparticles, with adjacent copper nanoparticles connected by surface contact.
[0038] This application also provides a solar cell, which includes the aforementioned electrode, and the electrode has a contact interface with the surface of the solar cell.
[0039] Furthermore, the region near the contact interface contains the copper nanoparticles.
[0040] Furthermore, the surface of the solar cell has a textured surface, and the electrode is located on the upper part of the textured surface of the solar cell.
[0041] Furthermore, within the electrode body, the volume content of nano-sized copper powder in the region near the contact interface is greater than the volume content in other regions of the electrode.
[0042] Furthermore, the surface of the sheet-like copper powder is attached to the electrode surface in a substantially horizontal state.
[0043] Furthermore, the flake copper powder is arranged at an angle α to the surface of the electrode, where 0°≤α≤50°.
[0044] Furthermore, the area of the orthographic projection of the sheet-like copper powder applied to the electrode surface accounts for 30%-65% of the electrode surface area.
[0045] The electrode and copper paste described in this application utilize nano-copper particles, which are composed of two or more copper nanoparticles connected together, to fill the voids between large-sized flake copper powders. The nano-copper particles have a three-dimensional shape with unequal diameters, which facilitates their matching with various shaped voids formed between multiple flake copper powders. Furthermore, their surfaces have more contact points with the flake copper powders and other nano-copper particles, increasing the contact area between the flake copper powders and the nano-copper particles, as well as among the copper particles themselves. This increases the conductive pathways between various conductive copper powders. The filling of nano-copper particles makes the electrode structure more compact, significantly reducing the electrode's bulk resistance and achieving conductivity comparable to electrodes prepared with silver paste. After sintering and curing, the nano-copper particles can also act as an auxiliary binder, improving the adhesion between the copper paste and the solar cell, resulting in a stronger connection between the electrode and the solar cell. Attached Figure Description
[0046] Figure 1 The image shows a scanning electron microscope (SEM) image of the electrode prepared in Example 1-1.
[0047] Figure 2 The image shows a scanning electron microscope (SEM) image of the electrode prepared in Example 1-1.
[0048] Figure 3 The image shows a scanning electron microscope (SEM) image of the electrode prepared in Example 2-1.
[0049] Figure 4 Scanning electron microscope image of the electrode provided in this application.
[0050] Figure 5 Scanning electron microscope image of the electrode provided in this application.
[0051] Figure 6 Scanning electron microscope image of the electrode provided in this application.
[0052] 1-Electrode body, 2-Electrode periphery, 3-Surface of the cell without electrode coverage. Detailed Implementation
[0053] The following description provides exemplary embodiments of this application, including various details to aid understanding, and should be considered merely exemplary. Therefore, those skilled in the art will recognize that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of this application. Similarly, for clarity and brevity, descriptions of well-known functions and structures are omitted in the following description.
[0054] This application provides an electrode comprising copper nanoparticles and sheet-like copper powder, wherein the copper nanoparticles comprise at least two connected copper nanoparticles, and adjacent copper nanoparticles are connected by surface contact.
[0055] In this paper, surface contact connection refers to a connection between two adjacent copper nanoparticles having at least two connection points or an overlap between two adjacent copper nanoparticles, wherein the maximum distance between the two connection points or the intersection arc length of the overlap is at least 10% of the diameter of either copper nanoparticle. In this application, the surface contact connection between two copper nanoparticles can be detected or observed by means of, for example, SEM or TEM.
[0056] In this application, nano-copper particles fill the gaps between the flake copper powders and are in direct contact with the flake copper powders, making the conductive channels between the conductive particles more unobstructed. Moreover, the filling of nano-copper particles makes the electrode structure more compact, significantly reducing the bulk resistance of the electrode and making it comparable to the conductivity of a silver electrode.
[0057] In this application, the median length of the copper nanoparticles is 150nm-700nm, and the median width of the copper nanoparticles is 40nm-400nm.
[0058] Specifically, the median length of the said copper nanoparticles can be 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, or 400nm.
[0059] Any value between 420nm, 450nm, 480nm, 500nm, 520nm, 550nm, 580nm, 600nm, 620nm, 650nm, 680nm, and 700nm.
[0060] Specifically, the median width of the said copper nanoparticles is 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm,
[0061] Any value between 260nm, 280nm, 300nm, 320nm, 340nm, 360nm, 380nm, and 400nm.
[0062] In this paper, the median length and median width of the copper nanoparticles are measured using SEM (Scanning Electron Microscopy). Ten different regions of the test sample are photographed, resulting in ten images. For each image, the dimensions of any ten copper nanoparticles observed are measured along their length. The median length of these ten nanoparticles is then calculated. Similarly, the dimensions along the width are measured, and the median width is calculated. Those skilled in the art will understand that the above method is merely exemplary, and they can appropriately reduce or increase the number or area of the selected copper nanoparticles based on actual conditions. For a single copper nanoparticle, the length direction corresponds to its longest length, and the width direction corresponds to the narrowest width among all cross-sections of the particle except the contact surface. The dimensions of various copper particles in the copper paste are also measured using SEM to determine their median values. The median values of both the flake-shaped and spherical copper powders described below are measured using this method.
[0063] In this application, the nano-copper particles are linear copper particles formed by at least two connected copper nanoparticles. The nano-copper particles can also be formed by bending and connecting at least two connected copper nanoparticles at a certain angle to form L-shaped, V-shaped, U-shaped, triangular, quadrilateral, W-shaped, or polygonal copper particles with 5 or more sides (polygonal copper particles with 5 or more sides can be pentagonal, hexagonal, heptagonal, etc.), preferably linear copper particles. In this document, the same electrode may simultaneously contain two or more of the following: linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, quadrilateral copper particles, W-shaped copper particles, or polygonal copper particles with 5 or more sides. For example, in some embodiments, the electrode contains linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, and triangular copper particles. In some embodiments, the electrode contains linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, and quadrilateral copper particles. In some embodiments, the electrode contains linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, and pentagonal copper particles. In some embodiments, the electrode contains linear copper particles, V-shaped copper particles, U-shaped copper particles, and triangular copper particles. In some embodiments, the electrode contains linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, and quadrilateral copper particles.
[0064] The copper nanoparticles described in this application have a three-dimensional shape with unequal diameters, which facilitates their matching with various shaped gaps formed between multiple flake copper powders. This effectively reduces the gaps formed by the flake copper powders and increases the conductive pathways between the copper powders. Especially for linear, L-shaped, and V-shaped copper particles, compared to spherical copper particles, they have more contact points with flake copper powders and other copper nanoparticles along their length, increasing the contact area between the flake copper powders and the copper nanoparticles, as well as among the copper nanoparticles themselves. This increases the conductive pathways between the copper powders, resulting in increased conductivity of the copper paste as an electrode. For triangular, quadrilateral, and polygonal copper particles, their ends have multiple protrusions formed by smaller copper nanoparticles, which act as bridges for electron conduction between the flake copper powders, similarly increasing the conductivity of the electrode.
[0065] Linear copper particles are defined as a string-like structure in which multiple connected copper nanoparticles are arranged in a face-to-face contact along the length direction. For example, when a linear copper particle is composed of two copper nanoparticles, it is gourd-shaped or peanut-shaped.
[0066] A bend-at-a-angle connection refers to multiple interconnected copper nanoparticles being connected in sequential face-to-face contact. In a certain position, the extension directions of two of the three interconnected copper nanoparticles (copper nanoparticle A, copper nanoparticle B, and copper nanoparticle C) are different from the extension directions of the other two interconnected copper nanoparticles, and they have a certain angle. That is, the extension direction of copper nanoparticle A after connecting with copper nanoparticle B is different from the extension direction of copper nanoparticle B after connecting with copper nanoparticle C, and they have a certain angle.
[0067] In the nano-copper particles, the number of copper nanoparticles can be 2, 3, 4, 5, or more, and multiple copper nanoparticles are connected in series.
[0068] In some embodiments, the copper nanoparticles are single-crystal phase copper nanoparticles with smooth surfaces.
[0069] In some embodiments, the copper nanoparticles are spherical or polyhedral, and the polyhedrons can be hexahedrons, octahedrons, etc.
[0070] In some embodiments, the copper nanoparticles are elemental copper or copper alloys. From the perspective of improving the oxidation resistance of copper, the copper alloys can be copper-silver alloys, copper-nickel alloys, copper-aluminum alloys, copper-tin alloys, etc.
[0071] The median particle size of copper nanoparticles is 40nm-400nm. In some embodiments, the median particle size of copper nanoparticles is 40nm-300nm. In some embodiments, the median particle size of copper nanoparticles is 50nm-200nm. In some embodiments, the median particle size of copper nanoparticles is 60nm-100nm.
[0072] Specifically, the median particle size of copper nanoparticles can be 40 nm, 60 nm, 80 nm,
[0073] Any value between 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, 340nm, 380nm, and 400nm.
[0074] In this application, the electrode further includes spherical copper powder.
[0075] In this paper, flake-shaped copper powder refers to copper powder with an aspect ratio (diameter / thickness) greater than or equal to 2 in images observed under a scanning microscope. The ratio of the longest diameter to the shortest diameter of the flake-shaped copper powder is 1-10. Spherical copper powder refers to copper powder with an aspect ratio (diameter / thickness) less than 2 in images observed under a scanning microscope.
[0076] In some embodiments, the copper powder contains 0.5%-15% by mass of the nano-copper particles, 35%-60% by mass of the flake-shaped copper powder, and 35%-60% by mass of the spherical copper powder.
[0077] Specifically, in the copper powder, the mass percentage of the nano-copper particles can be any value between 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, and 15%.
[0078] Specifically, in the copper powder, the mass percentage of the flake copper powder can be any value between 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, and 60%.
[0079] Specifically, in the copper powder, the mass percentage of the spherical copper powder can be any value between 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, and 60%.
[0080] Furthermore, the median diameter of the flake-shaped copper powder is 2μm-8μm, and the median thickness is 100nm-500nm. The median particle size of the spherical copper powder is 100nm-500nm.
[0081] Specifically, the median diameter of the flake copper powder can be any value between 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, and 8μm.
[0082] Specifically, the median thickness of the flake copper powder is any value between 100nm, 120nm, 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, 420nm, 450nm, 480nm, and 500nm.
[0083] Specifically, the median particle size of the spherical copper powder can be 100 nm, 120 nm, or...
[0084] Any value between 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, 420nm, 450nm, 480nm, and 500nm.
[0085] In this paper, nano-copper particles fill the gaps between flake copper powder and spherical copper powder, and are in direct contact with the flake copper powder and spherical copper powder. By coordinating the shape and / or mass of the flake copper powder, spherical copper powder and nano-copper particles, copper particles of various sizes and shapes are tightly packed, making the conductive channels between conductive particles more unobstructed.
[0086] In this application, the tap density of the flake copper powder is 4.4–5 g / ml, and the tap density of the spherical copper powder is 4.3–4.9 g / ml. The specific surface area of the flake copper powder is 0.4–0.7 m². 2 / g, the specific surface area of the spherical copper powder is 2.5-3.0m². 2 / g.
[0087] Specifically, the tap density of the flake copper powder can be any value between 4.4 g / ml, 4.5 g / ml, 4.6 g / ml, 4.7 g / ml, 4.8 g / ml, 4.9 g / ml, and 5 g / ml.
[0088] Specifically, the tap density of the spherical copper powder can be any value between 4.3 g / ml, 4.4 g / ml, 4.5 g / ml, 4.6 g / ml, 4.7 g / ml, 4.8 g / ml, and 4.9 g / ml.
[0089] Specifically, the specific surface area of the flake-shaped copper powder can be 0.4 m². 2 / g, 0.45m 2 / g, 0.5m 2 / g, 0.55m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 Any value between / g.
[0090] Specifically, the specific surface area of the spherical copper powder can be 2.5 m². 2 / g, 2.55m 2 / g, 2.60m 2 / g, 2.65m 2 / g, 2.70m 2 / g, 2.75m 2 / g, 2.80m 2 / g, 2.85m 2 / g, 2.90m 2 / g, 2.95m 2 / g, 3.0m 2 Any value between / g.
[0091] In this article, tap density, or bulk density of powder after compaction, refers to the density of powder after it has been packed into a specific container and the container has been vibrated to break up the voids in the powder and bring it into a tightly packed state. By measuring tap density, the flowability and porosity of the powder can be determined. It can be calculated by measuring the volume after 1000 vibrations using a BT-301 vibrator.
[0092] Specific surface area refers to the surface area per unit mass of a porous solid material. The commonly used unit is square meters per gram (m² / g). It can be tested using conventional methods, such as GB / T 13390-2008, "Determination of Specific Surface Area of Metal Powders".
[0093] In this application, the electrode comprises a main body portion and a peripheral portion, the peripheral portion being located on both sides of the main body portion, wherein the width of the peripheral portion on either side does not exceed 5%-50% of the width of the main body portion; the median copper powder particle size of the peripheral portion is less than the median copper powder particle size of the main body portion of the gate line.
[0094] In some embodiments, the main body portion and the peripheral portion extend in the same direction. The peripheral portion includes a first peripheral portion and a second peripheral portion, which are located on both sides of the main body portion and are symmetrically arranged with the extension direction of the main body portion as the axis of symmetry.
[0095] In some embodiments, the copper powder in the peripheral portion includes copper nanoparticles, and the copper powder in the main body portion includes copper nanoparticles and flake-shaped copper powder.
[0096] In some embodiments, the copper powder in the peripheral portion includes nano-copper particles and spherical copper powder, and the copper powder in the main body portion includes nano-copper particles, flake-shaped copper powder, and spherical copper powder.
[0097] In this application, no restrictions are placed on the method for measuring the width of the electrode body. The art can make conventional choices based on actual needs. For example, the width of the electrode body can be obtained by SEM measurement. For example, the width of the bottom of the copper electrode in a certain area within the field of view can be measured by SEM, and the average value can be calculated by continuously measuring 10 areas to obtain the width of the electrode body.
[0098] In this application, no limitation is made on the width of the outer portion of the electrode. Those skilled in the art can measure it using conventional methods in the art. For example, the width of the outer portion of the electrode can be measured by SEM. For example, since there is a significant difference in the height of copper powder coverage in the areas where the electrode body and the outer portion are located, and there is a significant difference in the particle size of copper powder in the two areas, the boundary line between the copper electrode body and the copper electrode outer portion can be found by SEM. This boundary line is used as the starting line of the outer portion of the electrode. Extending to both sides, the center of the area where the projected area of copper powder in a unit square centimeter area accounts for 30%-40% is used as the measurement endpoint. The vertical distance between the starting point and the endpoint relative to the straight line where the electrode is located is defined as the width of the outer portion. Ten measurement positions are randomly selected for measurement of a test sample of an electrode.
[0099] For example, the width of the outer portion on any side does not exceed 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% of the width of the main portion. Figure 1 This is a copper electrode in a specific embodiment of the present application, wherein 1 is the electrode body, 2 is the outer periphery of the electrode, and 3 is the surface of the battery cell without electrode coverage, and the width of the outer periphery of the electrode on any one side does not exceed 5%-50% of the width of the electrode body.
[0100] Figure 2 This is an electron microscope image of copper paste diffusion, from... Figure 2It can be seen that the copper powder in the copper paste diffuses into the pyramid-shaped textured surface to form a dense structure.
[0101] The electrode described in this application has peripheral portions of a certain width on both sides of the main body of the electrode. The median particle size of the copper powder in the peripheral portions is smaller than that in the main body. This allows for the formation of a dense structure in the peripheral portions, increasing the contact area between the electrode and the battery surface, improving the electrode's adhesion, and preventing water and oxygen from penetrating from the interface between the electrode and the bottom battery and oxidizing the copper powder in the main body. This reduces the bulk resistance of the electrode and the contact resistance between the electrode and the battery. Simultaneously, the width of the peripheral portion on any one side does not exceed 5%-50% of the width of the main body, ensuring that the electrode has low bulk resistivity and contact resistance, while also ensuring a low light shading rate.
[0102] In some embodiments, the present application does not impose any limitation on the width of the electrode body portion, and the width of a copper electrode body portion commonly used in the art can be adopted, wherein the width of the electrode body portion is 30-120 micrometers. In some embodiments, the width of the electrode periphery portion is 1-60 micrometers.
[0103] For example, the width of the electrode body portion can be 30 micrometers, 40 micrometers, 50 micrometers, 60 micrometers, 70 micrometers, 80 micrometers, 90 micrometers, 100 micrometers, 110 micrometers, 120 micrometers, etc.
[0104] For example, the width of the outer portion of the electrode can be 1 micrometer, 5 micrometers, 10 micrometers, 15 micrometers, 20 micrometers, 30 micrometers, 40 micrometers, 50 micrometers, 60 micrometers, etc.
[0105] In some embodiments, the height of the electrode body portion is 10-25 micrometers.
[0106] In this application, the height of the electrode body refers to the vertical height at the center point of the bottom edge of the electrode cross-section. This height is measured using SEM (Scanning Electron Microscopy). The vertical height at the center point of the bottom edge of the electrode cross-section is measured at any 20 locations on the test sample, and the average value is calculated; this average value is the height of the electrode body. Those skilled in the art will understand that the above method is merely exemplary, and they may appropriately reduce or increase the number of measurement locations for the selected electrode based on actual circumstances.
[0107] This application sets the height of the main body of the electrode, the width of the outer periphery, and the width of the main body within the above three numerical ranges. The resulting copper electrode can not only have a firm contact with the solar cell and reduce resistivity and improve current collection efficiency, but also have a small shading rate to light and reduce the cost of using the electrode.
[0108] In this application, the electrode is prepared by screen printing.
[0109] This application does not impose any limitations on the screen printing method. Those skilled in the art can use conventional methods to screen print copper paste. For example, the width of the electrode periphery and the width and height of the electrode body can be achieved by controlling the printing pressure, squeegee hardness, squeegee angle, paste solvent type, and solvent usage during screen printing. Those skilled in the art can obtain these process conditions through conventional optimization as needed.
[0110] This application also provides a copper paste comprising copper powder, the copper powder comprising nano-copper particles, flake copper powder, and optionally spherical copper powder, wherein the nano-copper particles comprise at least two connected copper nanoparticles, and adjacent copper nanoparticles are connected by surface contact.
[0111] The median length of the copper nanoparticles is 150nm-700nm. In some embodiments, the median length of the copper nanoparticles is 150nm-500nm, and in some embodiments, the median length of the copper nanoparticles is 150nm-400nm. The median width of the copper nanoparticles is 40nm-400nm. In some embodiments, the median width of the copper nanoparticles is 40nm-200nm, and in some embodiments, the median width of the copper nanoparticles is 40nm-100nm.
[0112] In this application, "optional" refers to the presence or absence of something. For example, in one embodiment, a copper paste of this application includes copper powder, which includes nano-copper particles and flake copper powder; in another embodiment, a copper paste of this application includes copper powder, which includes nano-copper particles, flake copper powder, and spherical copper powder.
[0113] In this application, the descriptions of the morphology, size, mass content, tap density, and specific surface area of the nano-copper particles, flake copper powder, and spherical copper powder in the copper paste can be referred to the descriptions of the nano-copper particles, flake copper powder, and spherical copper powder in the aforementioned electrodes.
[0114] In this paper, nano-copper particles fill the gaps between flake copper powder and spherical copper powder, and come into direct contact with the flake copper powder and spherical copper powder. By matching the shape and mass of the flake copper powder, spherical copper powder and nano-copper particles, copper particles of various sizes and shapes are tightly packed, making the conductive channels between conductive particles smoother.
[0115] In this paper, the surfaces of flake copper powder and spherical copper powder are coated with antioxidants. By coating the surface of copper powder with antioxidants, the copper powder in the copper paste is less likely to be oxidized. The method of forming the antioxidant layer is a conventional method, such as using antioxidants in a solution to treat acid-washed flake copper powder or spherical copper powder, so that the antioxidants are coated on the copper powder.
[0116] The antioxidant is selected from one or more compounds grouped together with fatty acids, amines, phosphoric acids, thiols, and polymers. The fatty acid compounds may include, but are not limited to, linear or branched C6-C22 saturated or unsaturated fatty acids, and these fatty acid compounds may be used alone or in combination of two or more. The amine compounds may include, but are not limited to, linear or branched C6-C22 aliphatic amines, and these amine compounds may be used alone or in combination of two or more. Furthermore, the phosphoric acid compounds may include, but are not limited to, phosphorous acid and its esters or salts, and hypophosphite and its esters or salts; the thiols may include, but are not limited to, ethanethiol, methanethiol, propanethiol, butanethiol, mercaptoethanol, etc. The polymers may include, but are not limited to, polyvinylpyrrolidone, polyvinyl butyral, carboxymethyl cellulose, and / or polyacrylic acid.
[0117] In this application, the copper paste further includes resin, solvent, curing agent, and optionally curing accelerator. The copper powder comprises 70-95 parts by weight, the resin comprises 5-15 parts by weight, the solvent comprises 5-20 parts by weight, the curing agent comprises 1-5 parts by weight, and the curing accelerator comprises 0-5 parts by weight. Specifically, in the copper paste, the weight percentage of copper powder can be any value between 70, 72, 74, 76, 78, 80, 82, 84, 86, 88, 90, 92, 94, and 95 parts.
[0118] Specifically, in the copper paste, the weight parts of resin can be any value between 5, 6, 7, 8, 9, 10, 11, 2, 13, 14, and 15 parts.
[0119] Specifically, in the copper paste, the weight of the solvent can be any value between 5, 6, 7, 8, 9, 10, 11, 2, 13, 14, 15, 16, 17, 18, 19, and 20 parts.
[0120] Specifically, in the copper paste, the weight of the curing agent can be any value between 1 part, 2 parts, 3 parts, 4 parts, and 5 parts.
[0121] Specifically, in the copper paste, the weight percentage of the curing agent accelerator can be any value between 0 parts, 1 part, 2 parts, 3 parts, 4 parts, and 5 parts.
[0122] Specifically, the resin is selected from one or more of epoxy resin, acrylic resin and phenolic resin, preferably epoxy resin.
[0123] Further, the epoxy resin is a thermosetting resin, selected from one or more of bisphenol A type epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A type epoxy resin, polyurethane modified epoxy resin, dimer acid modified epoxy resin, siloxane modified epoxy resin, phenolic type epoxy resin, polyol glycidyl ether type epoxy resin, and polybasic acid glycidyl ester type epoxy resin; preferably bisphenol A type epoxy resin or bisphenol F epoxy resin.
[0124] Specifically, the curing agent is selected from one or more of tertiary amines, isocyanates, imidazoles, dicyandiamides, and acid anhydrides; preferably tertiary amines; further, the tertiary amine is triethanolamine.
[0125] Furthermore, the isocyanate is selected from one or more of Trixene BI 7982 (blocked isocyanate based on HDI), MF-K60X (blocked polyisocyanate HDI curing agent), ketoxime-terminated isocyanate, hexamethylene diisocyanate-terminated with hexamethylene hexamethylene diisocyanate, and dodecyl mercaptan-terminated diphenyl diisocyanate.
[0126] Specifically, the solvent is selected from one or more of the following: divalent ester (DBE), diethylene glycol butyl ether, diethylene glycol butyl ether acetate, terpineol, dipropylene glycol butyl ether, and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, butyl acetate, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol dimethyl ether, dimethylformamide, N-methylpyrrolidone, diacetone alcohol, dimethylacetamide, γ-butyrolactone, butyl carbitol, butyl carbitol acetate, ethyl carbitol, ethyl carbitol acetate, dihydroterpineol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, dihydroterpineol acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate, preferably diethylene glycol butyl ether acetate.
[0127] Specifically, the curing accelerator catalyzes the curing of the resin, lowers the curing temperature, and shortens the curing time. The curing accelerator is selected from one of quaternary ammonium salts, imidazolium esters, imidazolium salts, or substituted ureas. Specifically, quaternary ammonium salts can be benzyltriethylammonium chloride, etc., and substituted ureas can be N-p-chlorophenyl-N,N'-dimethylurea, N-(3,4-dichlorophenyl)-N,N'-dimethylurea, N-(3-phenyl)-N,N'-dimethylurea, N-(4-phenyl)-N,N'-dimethylurea, etc. 2-Methylimidazole, etc.; imidazoles and their esters or imidazole salts can be imidazole sulfonates / salts, imidazole phosphates / salts or imidazole acetates / salts, such as dibutyl imidazole phosphate, 1-ethyl-3-methylimidazole acetate, 1-ethyl-3-methylimidazole methane sulfonate, trimellitate 1-cyanoethyl-2-undecapridinium, isocyanurate 2-methylimidazole, tetraphenylboronic acid 2-ethyl-4-methylimidazole and tetraphenylboronic acid 2-ethyl-1,4-dimethylimidazole.
[0128] In this application, the nano-copper particles can improve the rheological properties of the paste, enhance its smoothness and uniformity during printing, and their high surface area provides more contact points with other components in the paste (such as resin, solvent, etc.), which helps to improve the dispersibility and wettability of the powder in the paste, thus ensuring good printability of the paste.
[0129] This application also provides a method for preparing the above-mentioned copper paste, comprising the following steps:
[0130] Step 1: Preparation of nano-copper particles:
[0131] After mixing copper salt, reducing agent, dispersant and solvent, the mixture is gradually heated to a reaction temperature of 50-100℃, preferably 60-80℃, in a nitrogen atmosphere. The heating rate is 20-40℃ / hour, and the reaction is carried out for 2-15 hours, preferably 5-10 hours, at the reaction temperature.
[0132] The copper salt is a monovalent or divalent organic or inorganic copper salt, specifically selected from one or more of copper sulfate, anhydrous copper sulfate, copper carboxylate (copper formate, copper acetate, copper lactate, copper oxalate, copper tartrate, copper oleate, copper glycolate, copper oleate, copper stearate, copper myristate, copper citrate), copper chloride, and copper bromide.
[0133] The reducing agent is selected from at least one of sodium borohydride, hypophosphite, sodium hypophosphite, sodium phosphite, dimethylamineborane, amineborane, ascorbic acid, hydrazine hydrate, formic acid, oleylamine, and formaldehyde. Sodium borohydride or ascorbic acid is preferred.
[0134] The dispersant can be a compound that adsorbs copper nanoparticles. Examples include polymers such as polyvinyl alcohol, polyacrylic acid, polyvinylpyrrolidone, hydroxypropyl cellulose, propyl cellulose, and ethyl cellulose; chelating compounds such as ethylenediaminetetraacetic acid (EDTA), long-chain amines of iminodiacetic acid (e.g., C6-C16 alkylamines, such as hexylamine, octylamine, nonylamine, decylamine, undecylamine, dodecylamine, tridecylamine, tetradecylamine, pentadecylamine, hexadecylamine, trioctylamine, and dodecyldimethylamine); etc. Polyvinylpyrrolidone or polyacrylic acid is preferred.
[0135] The solvent is selected from one or more of the following: divalent ester (DBE), diethylene glycol butyl ether, diethylene glycol butyl ether acetate, terpineol, dipropylene glycol butyl ether, and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, butyl acetate, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether.
[0136] The molar ratio of the copper salt to the reducing agent is (1-2):(1-5).
[0137] In some embodiments, the molar ratio of the copper salt to the reducing agent is 1:(1-5), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 2:1, 2:3, 2:4, or 2:5.
[0138] Step 2: Mix the nano-copper particles with flake copper powder, optional spherical copper powder, resin, solvent, curing agent, and optional curing accelerator to obtain copper paste.
[0139] The median length of the copper nanoparticles is 150nm-700nm, and the median width of the copper nanoparticles is 40nm-400nm.
[0140] The proportions and weight parts of nano-copper particles, flake copper powder, optional spherical copper powder, resin, solvent, curing agent, and optional curing accelerator in step two can refer to the proportions and weight parts of nano-copper particles, flake copper powder, spherical copper powder, resin, solvent, curing agent, and curing accelerator in the aforementioned copper paste.
[0141] This application also provides another copper paste, comprising 70-95 parts by weight of copper powder, 5-15 parts by weight of resin, 1-5 parts by weight of curing agent, 1-3 parts by weight of reducing agent, 1-5 parts by weight of copper salt, 5-20 parts by weight of solvent and 0-5 parts by weight of curing accelerator.
[0142] The copper powder includes flake copper powder, and may further include spherical copper powder, wherein the mass percentage of the flake copper powder is 35%-60% and the mass percentage of the spherical copper powder is 35%-60%.
[0143] The parameters of the flake copper powder and spherical copper powder in the copper paste of this application can be referred to the foregoing description.
[0144] The types of resin, curing agent, solvent, and curing accelerator in the copper paste of this application can be referenced from the types of resin, curing agent, solvent, and curing accelerator in the aforementioned copper paste.
[0145] The reducing agent is selected from at least one of hypophosphite, sodium phosphite, hypophosphite (e.g., sodium hypophosphite, potassium hypophosphite, calcium hypophosphite, magnesium hypophosphite), dimethylamineborane, amineborane, glucose, hydrazine hydrate, formic acid, ethylene glycol, oleylamine, formaldehyde, and ammonia. Hypophosphite, hypophosphite, and formic acid are preferred. The copper salt is a monovalent or divalent organic or inorganic copper salt, specifically selected from one or more of copper sulfate, anhydrous copper sulfate, copper carboxylate (copper formate, copper acetate, copper propionate, copper butyrate, copper lactate, copper oxalate, copper glycolate, copper stearate, copper myristate), copper chloride, and copper bromide, preferably copper formate or copper citrate.
[0146] By combining the reducing agent and copper salt, the copper salt is reduced to nano-copper particles by the reducing agent when the slurry is heated and cured. By selecting the copper salt and reducing agent and controlling the reduction process, such as curing temperature and curing time, the reduction process is carried out simultaneously with the resin curing process of the slurry. In this way, the gaps between the flake and / or spherical powders become the reaction space for the reducing agent and copper salts, thereby forming the nano-copper particles of the shape of the present invention. At the same time, the nano-copper particles connect the flake copper powder and the spherical copper powder, improving the conductivity of the copper powder.
[0147] In this application, the surfaces of the flake copper powder and the spherical copper powder are coated with antioxidants, and the types and functions of the antioxidants can be referred to the foregoing description.
[0148] This application also provides a method for preparing the aforementioned copper paste, comprising the following steps:
[0149] We provide copper powder (including flake copper powder and spherical copper powder);
[0150] Copper paste is formed by mixing flake copper powder, spherical copper powder, copper salt, reducing agent, resin, solvent, curing agent and curing accelerator.
[0151] Specifically, 70-95 parts by weight of copper powder (of which 35-60 parts by weight of flake copper powder and 35-60 parts by weight of spherical copper powder), 5-15 parts by weight of resin, 1-5 parts by weight of curing agent, 1-3 parts by weight of reducing agent, 1-5 parts by weight of copper salt, 5-20 parts by weight of solvent and 1-5 parts by weight of curing accelerator are mixed and ground by a three-roll mill.
[0152] The types and sizes of the flake copper powder, spherical copper powder, copper salt, reducing agent, resin, solvent, curing agent, and curing agent accelerator in this preparation method can be referred to the description in the aforementioned copper paste.
[0153] This application also provides an electrode, wherein it is prepared by the aforementioned copper paste.
[0154] This application also provides a method for preparing the aforementioned electrode, comprising the following steps:
[0155] The aforementioned copper paste is heated and cured in a nitrogen atmosphere to obtain the electrode. The curing temperature is 100-200℃, for example, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, etc., and the curing time is 10min-60min, for example, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min, etc.
[0156] This application also provides a method for preparing the aforementioned electrode, including the following steps: pre-prepared copper paste is screen-printed onto a solar cell (e.g., HJT / HBC) with a grid line width of 40-120 μm, and then cured by heating in a nitrogen oven at a temperature of 100-200°C for 10-60 minutes to form an electrode grid line, which can be characterized by SEM electron microscopy.
[0157] This application also provides a solar cell, which includes the aforementioned electrode, and the electrode has a contact interface with the surface of the solar cell.
[0158] In this document, the area near the contact interface refers to the area 3 micrometers above the contact interface; the electrode body portion has the same meaning as the electrode body portion in the aforementioned electrode.
[0159] Furthermore, the area near the contact interface contains the nano-copper particles. The surface of the nano-copper particles described in this application has a large number of contact points, which can further increase the contact area between the electrode and the battery surface, reduce the contact resistance of the electrode, and improve the current collection capability of the solar cell.
[0160] The surface of the solar cell has a textured surface, and the electrode is located on the upper part of the textured surface of the solar cell.
[0161] In some embodiments, the solar cell has a textured surface structure that traps light to enhance solar radiation collection. The textured surface structure is a surface with a regular or irregular shape, used to scatter incident light and reduce the amount of light reflected back from the solar cell surface; specifically, it can be a pyramidal structure.
[0162] When the electrode comes into contact with the pyramid-shaped textured structure of the solar cell, the contact interface is located on the surface of the textured structure, and the area near the contact interface refers to the region of 3 micrometers above the base of the pyramid textured structure.
[0163] In some embodiments, within the electrode body portion, the volume content of nanoscale copper powder in the region near the contact interface is greater than the volume content in other regions of the electrode.
[0164] In this application, by controlling the volume content of nano-sized copper powder in the region near the contact interface to be greater than that in other regions of the electrode, the projected area of the nano-sized copper powder on the contact interface is made greater than that of the micron-sized flake copper powder on the contact interface. This allows the nano-sized copper powder to have a larger specific surface area and surface activity than the micron-sized flake copper powder, thereby enhancing the adhesion between the electrode and the surface of the solar cell, reducing the contact resistance of the electrode, and improving the current collection capability of the solar cell.
[0165] In this document, nanoscale copper powder refers to copper particles with a particle size distribution of 1-800 nm, and the shape is not limited. It may include the nanoscale copper particles and / or nanosphere powder of this application.
[0166] In some embodiments, the surface of the sheet-like copper powder is attached to the electrode surface in a substantially horizontal state.
[0167] In this paper, the electrode surface refers to the tangent line on the electrode surface where the sheet copper powder intersects with the electrode.
[0168] In this application, sheet-like copper powder with superior oxidation resistance is applied to the surface of the electrode in a near-horizontal or horizontal state to improve the overall oxidation resistance of the electrode when placed in the air and reduce the resistivity of the electrode.
[0169] Furthermore, the flake-shaped copper powder is arranged at an angle α to the surface of the electrode, where 0°≤α≤50°, in combination with... Figure 6 It can be seen that α is the tilt angle of the sheet-like copper powder on the electrode surface relative to the electrode surface.
[0170] In this paper, the α angle is measured using SEM (Scanning Electron Microscopy). A sheet of copper powder within the field of view is selected, and the midpoint of the intersection line between the horizontal plane of the sheet of copper powder and the electrode surface is chosen. A tangent line is drawn on the electrode surface using this midpoint, and the angle between the horizontal plane of the sheet of copper powder and this tangent line is calculated to obtain an α angle. The same method is used to measure the α angle of more than 10 sheet of copper powder in different regions of the test sample, and the average value of all measured α angles is calculated. Those skilled in the art will understand that the above method is merely exemplary, and they can appropriately reduce or increase the selected test sample area or number based on actual circumstances.
[0171] In some implementations, 0°≤α≤40°.
[0172] In some implementations, 0°≤α≤35°.
[0173] In some implementations, 0°≤α≤30°.
[0174] In some implementations, 0°≤α≤25°.
[0175] In some implementations, 5°≤α≤40°.
[0176] In some implementations, 5° ≤ α ≤ 35°.
[0177] In some implementations, 5° ≤ α ≤ 30°.
[0178] In some implementations, 5°≤α≤25°.
[0179] Specifically, α can be 50°, 45°, 42°, 40°, 38°, 35°, 32°, 30°, 28°, 25°, 22°, 20°, 18°, 15°, 12°, 10°, 8°, 5°, etc.
[0180] Furthermore, the area of the plate-like copper powder located on the electrode surface, as projected onto the electrode surface, accounts for 30%-65% of the electrode surface area.
[0181] In this application, the shape difference between sheet powder and ball powder can be further utilized to control the surface area ratio of sheet copper powder on the electrode surface, thereby improving the firmness of sheet powder on the surface and ensuring that the electrode has a high copper powder filling rate, and further reducing the resistivity of the electrode.
[0182] The projected area of the sheet-like copper powder on the electrode surface is obtained by SEM (Scanning Electron Microscopy). The electrode surface area is obtained by 3D microscopy, which measures the shape and size of the electrode to calculate its surface area. For example, when the electrode is the grid line of a solar cell, the cross-section of the electrode is trapezoidal or trapezoidal, and this cross-section is perpendicular to the extension direction of the electrode. The upper base a, lower base b, and height h of the trapezoid, as well as the length l of the electrode, are measured, and the surface area of the electrode is calculated using the following formula:
[0183]
[0184] Specifically, the area of the orthogonal projection of the sheet-like copper powder applied to the surface of the electrode relative to the surface area of the electrode can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, etc.
[0185] Furthermore, the solar cell is selected from one of BC cells, HJT cells, and perovskite / crystalline silicon tandem cells.
[0186] In some embodiments, the solar cell is a crystalline silicon cell, and a conductive barrier layer exists between the electrode and the crystalline silicon cell.
[0187] Copper ion diffusion into crystalline silicon solar cells can negatively impact cell performance. Copper ions affect the characteristics of the PN junction in crystalline silicon cells, leading to dark spot leakage (dark leakage) and a decrease in open-circuit voltage. This results in a decline in the overall efficiency and performance of the cell. In some implementations, the conductive barrier layer can be an oxide (e.g., a transparent conductive oxide such as aluminum oxide), a metal nitride (e.g., titanium nitride), or a metal (e.g., silver), or graphene, possessing excellent barrier properties. These conductive barrier layers can also be suitable conductive polymer films or other materials that can effectively prevent the diffusion of copper ions into crystalline silicon.
[0188] In some embodiments, the thickness of the conductive barrier layer is 5-500 nm, for example, it can be any value between 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, and 500 nm.
[0189] Example
[0190] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0191] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0192] Example 1-1
[0193] The electrode preparation method of this embodiment includes the following steps:
[0194] Step 1: Preparation of copper nanoparticles: Ascorbic acid, polyvinylpyrrolidone and ethanol are mixed to prepare a reducing agent solution. Then, an ethanol solution of copper citrate is added dropwise to the reducing agent solution. Under nitrogen protection, the mixture is gradually heated to 70°C (reaction temperature) at a heating rate of 20°C / hour. After reacting for 5 hours, the mixture is separated and purified to obtain copper nanoparticles. The copper nanoparticles are formed by two or more copper nanoparticles connected in face-to-face contact.
[0195] Step 2: Mix 1 part by weight of the prepared nano-copper particles with a solution of 50 parts by weight of flake copper powder, 40 parts by weight of spherical copper powder, 2 parts by weight of hydrogenated bisphenol A epoxy resin, 1.5 parts by weight of imidazole dibutyl phosphate, 1.5 parts by weight of blocked isocyanate and 5 parts by weight of diethylene glycol butyl ether solvent, and grind the mixture using a three-roll mill to obtain copper paste.
[0196] Step 3: Copper paste is screen-printed onto the solar cell wafer with a grid line width of 70 μm. It is then cured in a nitrogen oven at 190℃ to obtain the electrode grid lines. The microstructure of the grid lines, observed using a scanning electron microscope, is shown below. Figure 3 As shown, by Figure 3 It is known that the electrode grid line contains nano-copper particles, flake copper powder, and spherical copper powder. The nano-copper particles are formed by the contact connection of two or more copper nanoparticles, including linear copper particles, V-shaped copper particles, and polygonal copper particles. The nano-copper particles are distributed between large flake copper powder and spherical copper powder. In the region near the contact interface of the pyramid textured structure (the region 5 micrometers above the base of the pyramid), the content of nano-copper powder accounts for the vast majority. The volume content of nano-copper powder in the region near the contact interface of the pyramid textured structure is greater than that in other regions of the electrode.
[0197] The copper paste is screen-printed and cured into a copper film. Its sheet resistance R (mΩ) is measured with a four-probe sheet resistance meter, and its film thickness t (μm) is measured with a micrometer. Its resistivity ρ = R × t / 10.
[0198] The parameters of the electrode grid lines and copper paste are shown in Table 1.
[0199] The electrodes of Examples 1-2-1-3 differ from those of Example 1-1 in that the parameters of the sheet-like copper powder, spherical copper powder, and nano-copper particles are all different, while other parameters are the same. Specific parameters are shown in Table 1.
[0200] The electrodes of Examples 1-4 differ from those of Example 1-1 in that the parameters of the flake copper powder are different, while all other parameters are the same. See Table 1 for specific parameters.
[0201] The electrodes of Examples 1-5 differ from those of Example 1-1 in that the parameters of the spherical copper powder are different; all other parameters are the same. See Table 1 for specific parameters.
[0202] The electrode of Comparative Example 1-1 differs from that of Example 1-1 in that the parameters of the nano-copper particles are different, while all other parameters are the same. Specific parameters are shown in Table 1.
[0203] The electrodes of Comparative Examples 1-2 differ from those of Example 1-1 in that they do not contain flaky copper powder; all other parameters are the same. Specific parameters are shown in Table 1.
[0204] Table 1 shows the parameters for each embodiment and comparative example.
[0205]
[0206] Summary: As shown in Table 1, the copper paste described in this application uses nano-copper particles that fill the gaps between the flake-shaped and spherical copper powders and are in direct contact with them. Compared to spherical nano-copper particles, the nano-copper particles in this application make the conductive channels between conductive particles more unobstructed. Moreover, the filling of nano-copper particles makes the grid structure prepared from the copper paste more compact and significantly reduces the bulk resistance of the grid.
[0207] Example 2-1
[0208] The method for preparing the copper paste in this embodiment is as follows:
[0209] The following materials are provided: 50 parts by weight of flake copper powder and 40 parts by weight of spherical copper powder, 5 parts by weight of hydrogenated bisphenol A epoxy resin as resin, 1.5 parts by weight of imidazole dibutyl phosphate as curing accelerator, 1.5 parts by weight of blocked isocyanate as curing agent, 1 part by weight of formic acid as reducing agent, 1 part by weight of copper oxalate as copper salt, and 5 parts by weight of diethylene glycol butyl ether solvent; after the above materials are prepared in a certain proportion, they are ground into copper paste by a three-roll mill.
[0210] The prepared copper paste was screen-printed onto the solar cell with a grid line width of 70 μm. It was then cured in a nitrogen oven at 190°C to obtain the electrode grid lines. The microstructure of the grid lines was observed using a scanning electron microscope as follows: Figure 4-5 As shown, by Figure 4It is known that the electrode grid lines contain nano-copper particles, flake-shaped copper powder, and spherical copper powder. The nano-copper particles are formed by the fusion of two or more copper nanoparticles, including linear, V-shaped, and polygonal copper particles. These nano-copper particles are distributed between the large flake-shaped and spherical copper powder particles. Figure 5 It can be seen that the surface of the sheet copper powder is attached to the electrode surface in a basically horizontal state.
[0211] The copper paste was screen-printed and cured into a copper film. Its sheet resistance R (mΩ) was measured using a four-probe sheet resistance meter, and its film thickness t (μm) was measured using a micrometer. Its resistivity ρ = R × t / 10. The parameters of the electrode grid lines are shown in Table 2.
[0212] The electrodes in Examples 2-2 and 2-3 differ from those in Example 2-1 in that the parameters of the sheet-like copper powder, spherical copper powder, and nano-copper particles are all different, while other parameters are the same. Specific parameters are shown in Table 2.
[0213] The electrodes in Examples 2-4 differ from those in Example 2-1 in that the parameters of the sheet-like copper powder and the reducing agent used in the preparation of the nano-copper particles are different; all other parameters are the same. See Table 2 for specific parameters.
[0214] The difference between the electrodes in Examples 2-5 and Example 2-1 lies in the parameters of the spherical copper powder; all other parameters are the same. See Table 2 for specific parameters.
[0215] The electrodes in Examples 2-6 differ from those in Example 2-1 in that spherical copper powder is not added; all other parameters are the same. See Table 2 for specific parameters.
[0216] The electrode in Comparative Example 2-1 differs from that in Example 2-1 in that the parameters of the copper nanoparticles are different, while all other parameters are the same. Specific parameters are shown in Table 2.
[0217] The electrode in Comparative Example 2-2 differs from that in Example 2-1 in that it does not contain flake copper powder or nano-copper particles; all other parameters are the same. Specific parameters are shown in Table 2.
[0218] Table 2 shows the parameters for each embodiment and comparative example.
[0219]
[0220] Summary: As shown in Table 2, the copper paste described in this application, through the combination of reducing agent and copper salt, allows the copper salt to be reduced to the nano-copper particles of this application when the paste is heated and cured. These particles fill the gaps between the flake and / or spherical powders, and come into direct contact with the flake and spherical copper powders. Compared with spherical nano-copper particles, the nano-copper particles of this application make the conductive channels between conductive particles more unobstructed. Moreover, the filling of nano-copper particles makes the grid structure prepared from the copper paste more compact, which significantly reduces the bulk resistance of the grid.
[0221] Although the embodiments of this application have been described above, this application is not limited to the specific embodiments and application fields described above. The specific embodiments described above are merely illustrative and instructive, and not restrictive. Those skilled in the art can make many other forms based on the guidance of this specification and without departing from the scope of protection of the claims of this application, and these are all within the scope of protection of this application.
Claims
1. An electrode, wherein, It includes nano-copper particles and copper powder composed of flake copper powder and spherical copper powder. The nano-copper particles include at least two connected copper nanoparticles, which fill the void area between the copper powders. The adjacent copper nanoparticles are connected by surface contact. The copper nanoparticles are linear copper particles formed by at least two connected copper nanoparticles; and / or The copper nanoparticles are formed by bending and connecting at least two connected copper nanoparticles at a certain angle to form L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, quadrilateral copper particles, W-shaped copper particles, or polygonal copper particles with more than 5 sides.
2. The electrode according to claim 1, wherein, The median length of the copper nanoparticles is 150nm-700nm, and the median width of the copper nanoparticles is 40nm-400nm.
3. The electrode according to claim 1, wherein, The mass percentage of the nano-copper particles is 0.5%-15%, the mass percentage of the flake copper powder is 35%-60%, and the mass percentage of the spherical copper powder is 35%-60%.
4. The electrode according to claim 1, wherein, The median particle size of the spherical copper powder is 100nm-500nm.
5. The electrode according to claim 1, wherein, The tap density of the flake copper powder is 4.4~5 g / ml, and the tap density of the spherical copper powder is 4.3~4.9 g / ml; or The specific surface area of the flaky copper powder is 0.4~0.7m². 2 / g, the specific surface area of the spherical copper powder is 2.5~3.0m². 2 / g.
6. The electrode according to claim 1, wherein, The median diameter of the flake copper powder is 2μm-8μm, and the median thickness is 100nm-500nm.
7. The electrode according to claim 1, wherein, The electrode comprises a main body portion and a peripheral portion, the peripheral portion being located on both sides of the main body portion, wherein the width of the peripheral portion on either side does not exceed 5%-50% of the width of the main body portion; the median copper powder particle size of the peripheral portion is less than the median copper powder particle size of the main body portion of the gate line.
8. The electrode according to claim 7, wherein, The copper powder in the outer portion includes the nano-copper particles, and the copper powder in the main body portion includes the flake-shaped copper powder and the nano-copper particles.
9. The electrode according to claim 7, wherein, The width of the main body portion is 30-120 micrometers; or the width of the peripheral portion is 1-60 micrometers.
10. The electrode according to any one of claims 1-9, wherein, The electrode is prepared by screen printing.
11. A copper paste, wherein, It includes copper nanoparticles, flake copper powder, and optionally spherical copper powder, wherein the copper nanoparticles include at least two connected copper nanoparticles, and the adjacent copper nanoparticles are connected by surface contact. The copper nanoparticles are linear copper particles formed by at least two connected copper nanoparticles; and / or The copper nanoparticles are formed by bending and connecting at least two connected copper nanoparticles at a certain angle to form L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, quadrilateral copper particles, W-shaped copper particles, or polygonal copper particles with more than 5 sides.
12. The copper paste according to claim 11, wherein, The median length of the copper nanoparticles is 150nm-700nm, and the median width of the copper nanoparticles is 40nm-400nm.
13. The copper paste according to claim 11, wherein, The mass percentage of the nano-copper particles is 0.5%-15%, the mass percentage of the flake copper powder is 35%-60%, and the mass percentage of the spherical copper powder is 35%-60%.
14. The copper paste according to claim 13, wherein, The median diameter of the flake-shaped copper powder is 2μm-8μm, and the median thickness is 100nm-500nm; or The median particle size of the spherical copper powder is 100nm-500nm.
15. The copper paste according to claim 13, wherein, The tap density of the flake copper powder is 4.4~5 g / ml, and the tap density of the spherical copper powder is 4.3~4.9 g / ml; or The specific surface area of the flaky copper powder is 0.4~0.7m². 2 / g, the specific surface area of the spherical copper powder is 2.5~3.0m². 2 / g.
16. The copper paste according to any one of claims 11-15, wherein, The copper paste further includes resin, solvent, curing agent, and optionally a curing accelerator. The copper powder comprises 70-95 parts by weight, the resin comprises 5-15 parts by weight, the curing agent comprises 1-5 parts by weight, the solvent comprises 5-20 parts by weight, and the curing accelerator comprises 0-5 parts by weight; or, The resin is selected from one or more of epoxy resin, acrylic resin, and phenolic resin; or, The curing agent is selected from one or more of tertiary amine, isocyanate, imidazole, dicyandiamide, and acid anhydride curing agents; or, The optional curing accelerator is a quaternary ammonium salt, an imidazolium ester, an imidazolium salt, or a substituted urea; or, The solvent is selected from one or more of the following: divalent ester (DBE), diethylene glycol butyl ether, diethylene glycol butyl ether acetate, terpineol, dipropylene glycol butyl ether, and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, butyl acetate, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol dimethyl ether, dimethylformamide, N-methylpyrrolidone, diacetone alcohol, dimethylacetamide, γ-butyrolactone, butyl carbitol, butyl carbitol acetate, ethyl carbitol, ethyl carbitol acetate, dihydroterpineol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, dihydroterpineol acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.
17. An electrode, wherein, The electrode is obtained by screen printing the copper paste according to any one of claims 11-16, wherein the copper nanoparticles fill the void regions between the copper powders.
18. A method for preparing copper paste according to any one of claims 11-16, wherein, Includes the following steps: Preparation of copper nanoparticles; Copper paste is prepared by mixing nano-copper particles with flake copper powder, spherical copper powder, resin, solvent, curing agent and optional curing accelerator. The copper nanoparticles comprise at least two connected copper nanoparticles, which are connected by surface contact.
19. A solar cell, wherein, Includes the electrode as described in any one of claims 1-10 or 17, wherein the electrode has a contact interface with the surface of the solar cell.
20. The solar cell of claim 19, wherein the region near the contact interface contains the copper nanoparticles.
21. The solar cell according to claim 19 or 20, wherein, The surface of the solar cell has a textured surface, and the electrode is located on the upper part of the textured surface of the solar cell.
22. The solar cell according to claim 19 or 20, wherein, Within the electrode body, the volume content of nano-sized copper powder in the region near the contact interface is greater than the volume content in other regions of the electrode.
23. The solar cell according to claim 19, wherein, The surface of the sheet-like copper powder is attached to the electrode surface in a basically horizontal state.
24. The solar cell according to claim 23, wherein, The flake-shaped copper powder is arranged at an angle α to the surface of the electrode, where 0°≤α≤50°.
25. The solar cell according to claim 23, wherein, The area of the sheet-like copper powder applied to the electrode surface, as projected onto the electrode surface, accounts for 30%-65% of the electrode surface area.
Citation Information
Patent Citations
Conductive paste composition for low temperature firing
CN103021512A